Minimum effective local anesthetic volume for surgical anesthesia by subparaneural, ultrasound-guided popliteal sciatic nerve block: A prospective dose-finding study. Issue 34 (August 2016) - Bang, Seung Uk; Kim, Dong Ju; Bae, Jin Ho; Chung, Kyudon; Kim, Yeesuk
Abstract : Abstract: Because of its rapid onset time, recent years have seen an increase in the use of ultrasound (US)-guided popliteal sciatic nerve block (PSNB) via subparaneural injection for induction of surgical anesthesia. Moreover, in below-knee surgery, combined blocks, as opposed to sciatic nerve block alone, have become more common. These combined blocks often require a large volume of local anesthetic (LA), thus increasing the risk of local-anesthetic systemic toxicity (LAST). Thus, to decrease the risk of LAST, it is important to know the minimum effective volume (MEV) required for an adequate block. We, therefore, aimed to determine the MEV of ropivacaine 0.75% for induction of surgical anesthesia by the method of US-guided popliteal sciatic nerve block via subparaneural injection. Thirty patients underwent a US-guided PSNB with ropivacaine 0.75% at a 20-mL starting volume. Using a step-up/step-down method, we determined injection volumes for consecutive patients from the preceding patient's outcome. When an effective block was achieved within 40 minutes after injection, the next patient's volume was decreased by 2 mL. If the block failed, the next patient's volume was increased by 2 mL. The sensory and motor blockade was graded according to a 4-point scale. The block was considered a success if a combination of anesthesia and paresis (a score of 3 for both the sensory and motor nerves) was achieved within 40 minutes. The primary outcome measure was the MEV resulting in a successful subparaneural block of the sciatic nerve in 50% of patients (MEV50 ). Additionally, the data were processed with a probit regression analysis to determine the volume required to produce a complete sciatic nerve block in 90% of subjects (ED90 ). The MEV50 of 0.75% ropivacaine is 6.14 mL (95% confidence interval, 4.33–7.94 mL). The ED90 by probit analysis for a subparaneural injection was 8.9 mL (95% CI, 7.09–21.75 mL). The 6.14-mL MEV50 of ropivacaine 0.75% represents a 71% reduction in volume compared with neurostimulation techniques and a 14.7% reduction in volume compared with US-guided PSNB using the alternative perineural injection technique.